2015
DOI: 10.4103/0974-1208.158618
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue-derived mesenchymal stem cells repair germinal cells of seminiferous tubules of busulfan-induced azoospermic rats

Abstract: CONTEXT:Adipose tissue-derived mesenchymal stem cells (AT-MSCs) are less invasive than bone marrow mesenchymal stem cells to obtain for cell therapy.AIMS:The aims of this study were to evaluate the germinal cells characteristics and repairs in seminiferous tubules of busulfan-induced azoospermic rats after AT-MSCs transplantation.SETTINGS AND DESIGN:Experimental case-control study.MATERIALS AND METHODS:In the present experimental study, donors AT-MSCs were isolated from subcutaneous adipose tissue of two Sprag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Allogeneic BM-MSCs trans-differentiated into spermatogenic-like-cells and enhanced endogenous fertility recovery in rat by injection into seminiferous tubules of recipient with busulfan induced ( 2 , 19 , 31 ) and testicular torsion ( 32 ) azoospermia rat. Mehrabani et al ( 33 ) and Cakici et al ( 18 ) demonstrated that adipose-tissue-derived MSCs can leading to recovery of fertility in the busulfan-treated azoospermia rat model. Recently, Chen et al ( 34 ) showed that sperm differentiation potential of transplantation of human umbilical cord MSCs into immunodeficient mouse seminiferous tubule.…”
Section: Discussionmentioning
confidence: 99%
“…Allogeneic BM-MSCs trans-differentiated into spermatogenic-like-cells and enhanced endogenous fertility recovery in rat by injection into seminiferous tubules of recipient with busulfan induced ( 2 , 19 , 31 ) and testicular torsion ( 32 ) azoospermia rat. Mehrabani et al ( 33 ) and Cakici et al ( 18 ) demonstrated that adipose-tissue-derived MSCs can leading to recovery of fertility in the busulfan-treated azoospermia rat model. Recently, Chen et al ( 34 ) showed that sperm differentiation potential of transplantation of human umbilical cord MSCs into immunodeficient mouse seminiferous tubule.…”
Section: Discussionmentioning
confidence: 99%
“…The intertubular portions of the seminiferous tubules are involved in providing blood and immune responses. [12][13][14] Leydig cells are one of the most important cells in testis that are the source of testicular testosterone and insulin-like factor 3. In addition to Leydig cells, intercellular components include immune cells, lymphatic and blood vessels, nerves, connective tissue, and fibroblasts.…”
Section: Male's Reproductive Organmentioning
confidence: 99%
“…They are one of the suitable options for cell therapy for many diseases such as infertility (5). In recent years, researchers developed a new method to treat infertility by differentiating stem cells into male and female germ cells in vitro and in vivo; they took promising steps toward treatment of infertility (6,7). The important limitations of clinical applications of stem cells are the small number of cells and their differentiation into undesirable lineage in vitro (8,9).…”
Section: Introductionmentioning
confidence: 99%